Post a New Question

Algebra

posted by on .

I have a question I have this systems to solve

2x-y = 1
3x-3=y

How do I go about solving this?
Please give me some direction

  • Algebra - ,

    sub the 2nd into the 1st

    2x - y = 1
    2x - (3x-3) = 1
    2x - 3x + 3 = 1
    -x = -2
    x = 2

    back into the 2nd
    3(2)-3 = y
    y = 3

  • Algebra - ,

    Thank you

Answer This Question

First Name:
School Subject:
Answer:

Related Questions

More Related Questions

Post a New Question